The Role of Senescence-Associated Secretory Phenotype in Bone Loss - Zhu, Runjiu; Wan, Haoyang; Yang, Hong; Song, Mingrui; Chai, Yu; Yu, Bin (Frontiers in Cell and Developmental Biology, 2022)
As the population of most nations have a large proportion of older individuals, there is an increase in the prevalence of osteoporosis. Consequently, scientists have focused their attention on the pathogenic mechanisms of osteoporosis. Owing to an increase in studies on cellular senescence in recent years, research has begun to focus on the function of the senescent microenvironment in osteoporosis. With chronic inflammation, senescent cells in the bone marrow secrete a series of factors known as senescence-associated secretory phenotype (SASP) factors, acting on their own or surrounding healthy cells and consequently exacerbating ageing.The components of the SASP may differ depending on the cause of osteoporosis. This review aimed to summarize the relationship between SASP factors and osteoporosis and suggest new insights into the mechanistic investigation of osteoporosis.